Argumentum ex Cartesio: A Study of Descartes’ Employment of Arguments in His Meditations on First Philosophy - Tweyman, Stanley (European Journal of Social Science Education and Research, 2023)
In his Regulae (Rules for the Direction of the Understanding), Descartes focuses on Arithmetic and Geometry as the methodological model for argumentation and learning generally. As a result, it is generally assumed that his Meditations on First Philosophy employs the deductive method utilized in Mathematics. Part of the difficulty in understanding the method of the Meditations stems from the fact the nowhere in the Meditations does Descartes explain the method he employs in this work. In fact, Descartes addresses the method of the Meditations in only one place, namely, in the Replies to the Second Set of Objections, where he contrasts the method of Geometry (which he refers to as ‘synthesis’) with the method of the Meditations (which he refers to as ‘analysis’). In my paper, I turn to the Descartes’ Dreaming/ Waking argument in the fourth and fifth paragraphs of the first meditation to illustrate how scholars have erred in their critical exegetical efforts, when they regard the Meditations as utilizing a logical mathematical-type approach in arguments in the search after truth. In the second half of my paper, I focus on Descartes’ method of ‘analysis’, the only method that he insists he employs in his Meditations.
Keywords: dreaming, waking, method, argument, deduction, hyperbolic doubt